The determinants of participation in physical activity in Malaysia - Cheah, Yong Kang (Elsevier Korea LLC, 2014)
Objectives: In light of the importance of physical activity, the aim of the present study is to examine the factors affecting participation in physical activity among adults in Malaysia. Methods: A logistic regression model and the Third National Health and Morbidity Survey consisting of 30,992 respondents were used.Results: Age, income, gender, education, marital status, region, house locality,job characteristics, and medical conditions are significantly associated with participation in physical activity.In particular, old individuals, high income earners, females, the well-educated, widowed or divorced individuals, East Malaysians, urban dwellers, the unemployed, and individuals who are not diagnosed with hypercholesterolemia are less likely to be physically active than others. Conclusion: Because sociodemographic and health factors play an important role in determining physical activity, the government should take them into account when formulating policy.